Increased expression of hypoxia-inducible factor-1 alpha and its impact on transcriptional changes and prognosis in malignant tumours of the ocular adnexa. (November 2018) - Lange, Clemens; Lehnert, Patrick; Boneva, Stefaniya; Zhang, Peipei; Ludwig, Franziska; Boeker, Martin; Hoffmeier, Klaus; Horres, Ralf; Schlunck, Günther; Reinhard, Thomas; Böhringer, Daniel; Auw-Haedrich, Claudia
Abstract Purpose To investigate the expression profile of the hypoxia-inducible transcription factor-1α (HIF-1α) and its downstream targets in malignancies of the ocular adnexa and to determine its relevance as a prognostic factor for clinical outcome. Methods We included 49 subjects with malignant tumours (25 squamous cell carcinomas (SCC), 15 non-Hodgkin lymphomas, 9 melanomas) and 30 patients with benign tumours of the ocular adnexa (13 papillomas, 7 reactive lymphoid hyperplasias (RLHs) and 10 nevi) as controls. We quantified HIF-1α protein expression by immunohistochemistry and assessed the association between HIF-1α and clinical outcome via Kaplan–Meier analysis. Furthermore, we assessed the expression of HIF-1α downstream factors by transcriptional sequencing using the MACE (massive analysis of cDNA ends) technology. Results SCCs revealed a strong HIF-1α expression in 61% of tumour cells in comparison with only 22% in papillomas (p  < 0.0001). In contrast, malignant melanomas and lymphomas revealed a similar HIF-1α expression compared with nevi and RLHs. Transcriptional sequencing and Gene Ontology Cluster analysis demonstrated 37 hypoxia-associated factors, including HIF-1α, VEGF, SFRP1 and LOXL2 that are significantly increased in SCC and may contribute to tumour proliferation, angiogenesis, and metastasis. Association analysis between HIF-1α immunoreactivity and clinical outcome revealed a trend towards an unfavourable prognosis in malignant tumours with increased HIF-1α expression. Conclusions HIF-1α protein is increased in malignant tumours of the ocular adnexa, which is associated with an increase in multiple HIF-1α-downstream factors and a trend towards an unfavourable clinical outcome.